Comparative analysis of life history traits and trends of abundance in coral reefs of the orange-spotted grouper (Epinephelus coioides) from two regions of the Arabian Gulf. (4th February 2019) - Lin, Yu-Jia; Grandcourt, Edwin M; Rabaoui, Lotfi; Maneja, Rommel H; Qurban, Mohammad A; Al-Abdulkader, Khaled; Roa-Ureta, Rubén H
Abstract: The orange-spotted grouper Epinephelus coioides is one of the most important commercially exploited fish species in the Arabian Gulf. Studies to establish the basic biological knowledge necessary for sustainable exploitation are few and of limited spatial extent. We carry out a comparative analysis of life history traits of this sequential hermaphrodite and of trends of abundance in coral reefs, northern vs. southern Gulf. We found remarkable differences in sex proportion by length and age, rates of somatic growth, size at maturity and production of gonadic biomass, and no differences in the age composition, mode of growth, timing and duration of spawning, natural mortality rate, and trends of abundance. In the northern Gulf, the reproductive tactics could be diandric protogyny or protandric because males disappear at higher size and later age. In the southern Gulf, the strategy is protogyny, with full predominance of females in early life and full predominance of males in late life. In the northern Gulf, the orange-spotted grouper could exhibit bidirectional sex change. We suggest that fisheries policies should be versatile, consisting of regional-wide as well as local management measures, to account for local differences and regional-wide commonalities in life history traits and trends of abundance.